Zionisme dan Peranannya Dalam Kejatuhan Turki Uthmaniyah: Zionism and Its Role In the Fall of the Ottoman Empire - Zaki, Husna Khaleedah; Azman, Iffah Syadiyah; Yusnan, Muhammad Ridhuan; Mohd Nor, Mohd Roslan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
This article explores the complex role of Zionism in the political and territorial decline of the Ottoman Empire. Drawing on historical accounts, archival documents, and scholarly analyses, the study examines the emergence of the Zionist movement in the late 19th century and its interplay with the geopolitical dynamics of the Ottoman era. It investigates the socio-political aspirations of Zionist leaders, the impact of European colonial interests, and the response of Ottoman authorities to the increasing migration and settlement of Jewish communities in Palestine. The analysis highlights how Zionist ambitions aligned with external pressures, including European powers’ strategic exploitation of Ottoman weaknesses, contributing to internal destabilization and territorial fragmentation. By contextualizing Zionism within the broader spectrum of imperial decline, the article provides a nuanced understanding of the interplay between ideological movements, foreign intervention, and domestic challenges in the disintegration of one of history’s most enduring empires. This study offers valuable insights into the historical foundations of contemporary Middle Eastern conflicts and their roots in the late Ottoman period.